Sulforaphane Promotes Dendritic Cell Stimulatory Capacity Through Modulation of Regulatory Molecules, JAK/STAT3- and MicroRNA-Signaling - Wang, Yangyi; Petrikova, Emilia; Gross, Wolfgang; Sticht, Carsten; Gretz, Norbert; Herr, Ingrid; Karakhanova, Svetlana (Frontiers in Immunology, 2020)
Introduction The broccoli isothiocyanate sulforaphane was shown to inhibit inflammation and tumor progression, also in pancreatic cancer, while its effect on tumor immunity is poorly understood. We investigated the immunoregulatory effect of sulforaphane on human dendritic cells alone and in presence of pancreatic tumor antigens, as well as underlying molecular mechanisms. Methods Sulforaphane-treated human dendritic cells were matured in vitro with a cytokine cocktail, and the expression of regulatory molecules was examined by flow cytometry. The subsequent T-cell response was analyzed by T-cell proliferation assay and CD25 expression. To confirm the findings, dendritic cells pulsed with pancreatic cancer-derived tumor antigens were used. To identify the involved pathway- and microRNA-signaling in sulforaphane-treated dendritic cells, inhibitors of various signaling pathways, western blot analysis, microRNA array, and bioinformatic analysis were applied. Results Sulforaphane modulated the expression of the costimulatory CD80, CD83 and the suppressive B7-H1 molecules on dendritic cells and thereby promoted activation of T cells. The effect was verified in presence of pancreatic tumor antigens. Phosphorylation of STAT3 in dendritic cells was diminished by sulforaphane, and the inhibition of JAK/STAT3 led to downregulation of B7-H1 expression. Among the identified top 100 significant microRNA candidates, the inhibition of miR-155-5p, important for the expression of costimulatory molecules, and the induction of miR-194-5p, targeting the B7-H1 gene, were induced by sulforaphane. Conclusion Our findings demonstrate that sulforaphane promotes T-cell activation by dendritic cells through the modulation of regulatory molecules, JAK/STAT3- and microRNA-signaling in healthy conditions and in context of pancreatic cancer-derived antigens. They explore the immunoregulatory properties of sulforaphane and justify further research on nutritional strategies in the co-treatment of cancer.